Creating a culture of caring: A collaborative academic‐practice approach to clinical education. Issue 3 (18th March 2019) - Gierach, Michelle; Knuppe, Michelle; Winterboer, Venita; Randall, Robin
Abstract: Strong academic and practice partnerships are needed in the ever‐changing health care environment. Sometimes an invisible barrier exists between clinical practice and academia; academic‐practice partnerships are a way to bridge this barrier. Since 2008a team‐based model of clinical education known as the Culture of Caring (COC) has brought together three academic institutions with a large hospital system to develop a unified clinical experience and curriculum that improves the student, provider, and patient experience. In the COC model the team consists of academic‐practice leaders, clinical instructors, staff nurses, and students. Together they engage in a structured curriculum that is integrated into both the clinical environment and the academic setting. Each week of clinical the students focus on a topic that is paired with journal articles and learning activities that allow the team to engage in learning that is applicable to the clinical practice environment. The learning activities allow students to engage in learning about evidence‐based practice and quality improvement initiatives that are taking place on the unit. The implementation of this collaborative approach to a clinical nursing education model has had a positive impact on the working relationships between the academic partners and clinical practice leaders.